PENGARUH PROJECT BASED LEARNING DALAM PROYEK PENGUATAN PROFIL PELAJAR PANCASILA TERHADAP KREATIVITAS SISWA KELAS V DI SDN 176 PALEMBANG - Nadia Zahirah; Kabib Sholeh; Sylvia Lara Syaflin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is motivated by the problem of low student creativity and lack ofmotivation to actively participate in learning, especially in the subject of thePancasila Learner Profile Strengthening Project (P5) at Public Elementary School176 Palembang. The purpose of this study is to examine the effect of ProjectBased Learning in the Pancasila Learner Profile Strengthening Project onstudents’ creativity in entrepreneurship-themed material with the project topic“learning to become an entrepreneur” (making handicrafts from recycledmaterials). The research subjects were fifth-grade students at Public ElementarySchool 176 Palembang. This quantitative study used a True Experimental Designwith a Posttest-Only Control Group Design. Data collection techniques includedobservation, interviews, questionnaires, creativity product assessment sheets, anddocumentation. Data analysis involved normality tests, homogeneity tests, andhypothesis testing. The results of the Kolmogorov-Smirnov and Shapiro-Wilk testsshowed a significance value (Sig.) > 0.05, indicating normal data distribution. Thehomogeneity test showed a significance value of 0.249, meaning the data werehomogeneous. The creativity questionnaire data were then analyzed using anIndependent Sample T-test, which showed a significance value (2-tailed) of 0.000< 0.05, meaning the null hypothesis was rejected and the alternative hypothesiswas accepted. Thus, it can be concluded that Project Based Learning in thePancasila Learner Profile Strengthening Project has a significant effect on thecreativity of fifth-grade students at Public Elementary School 176 Palembang.